(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Injudicious application of nitrogenous fertilizers leads to soil quality deterioration which results into yield loss. The application of biofertilizer containing native efficient rhizobia enhances the nodular properties, N-fixation and soil quality. Therefore, fifty strains of Rhizobium were isolated from root nodule of Raikia french bean and among them only two isolates viz., RBHR-15 and RBHR-21 were confirmed as Rhizobium. The isolates were unable to grow under anaerobic conditions and failed to produce ketolactase enzyme, showed a negative response for gelatin liquefaction and Simmon’s citrate agar test, responded positively towards the indole test, MR-VP, TSI test and could produce NH4+ from peptone in the growth medium. The isolate RBHR-15, could reduce H2S and nitrate whereas, RBHR-21 could not. The growth of both isolates was luxuriant in the nutrient broth containing 1% NaCl and decreased with an increase in the concentration of NaCl and grew profusely in the pH range of 6-8. The generation time of RBHR-15 and RBHR-21 were 16.4and 10.6 h, respectively. The 16s rRNA of both isolates was sequenced and submitted to the National Center for Biotechnology Information (NCBI). The isolates RBHR-15, and RBHR-21 were assigned accession numbers MN480514 and MN480516.